An in vitro model to assess the immunosuppressive effect of tick saliva on the mobilization of inflammatory monocyte-derived cells. (December 2015) - Vachiery, Nathalie; Puech, Carinne; Cavelier, Patricia; Rodrigues, Valérie; Aprelon, Rosalie; Lefrançois, Thierry; Martinez, Dominique; Epardaud, Mathieu
Abstract Tick-borne pathogens cause potent infections. These pathogens benefit from molecules contained in tick saliva that have evolved to modulate host innate and adaptive immune responses. This is called "saliva-activated transmission" and enables tick-borne pathogens to evade host immune responses. Ticks feed on their host for relatively long periods; thus, mechanisms counteracting the inflammation-driven recruitment and activation of innate effector cells at the bite site, are an effective strategy to escape the immune response. Here, we developed an original in vitro model to evaluate and to characterize the immunomodulatory effects of tick saliva that prevent the establishment of a local inflammatory immune response. This model mimics the tick bite and enables the assessment of the effect of saliva on the inflammatory-associated dynamic recruitment of cells from the mononuclear phagocyte system. Using this model, we were able to recapitulate the dual effect of tick saliva on the mobilization of inflammatory monocyte-derived cells, i.e. (i) impaired recruitment of monocytes from the blood to the bite wound; and (ii) poor mobilization of monocyte-derived cells from the skin to the draining lymph node. This simple tool reconstitutes the effect of tick saliva in vivo, which we characterized in the mouse, and should enable the identification of important factors facilitating pathogen infection. Furthermore, this model may be applied to the characterization of any pathogen-derived immunosuppressive molecule affecting the establishment of the inflammatory immune response.